Diagnostic Values of Dermatoscopy and CD31 Expression in Cutaneous Lymphangioma Circumscriptum - Lu, Lixia; Yan, Siyu; Chen, Mingliang; Huang, Xiaoyan; Su, Juan (Frontiers in Medicine, 2021)
Abstract Background Cutaneous lymphangioma circumscriptum (CLC) is characterized by clusters of deep-seated, vesicle-like papules. CLC is not a tumor but rather a congenital malformation of superficial lymphatics. Abstract Background Cutaneous lymphangioma circumscriptum (CLC) is characterized by clusters of deep-seated, vesicle-like papules. CLC is not a tumor but rather a congenital malformation of superficial lymphatics. Objectives The study aimed to describe the dermoscopic features of CLC and investigate why marked blood components in CLC. Moreover, this study sought to increase awareness of the clinical characteristics of CLC and provide insights into CLC diagnosis. Methods A representative sample of patients CLC with demographic information, pathological and dermoscopical results were analysed. Immunohistochemistry of lymphangioma specimens with CD31 and D2-40 were performed. Clinical manifestations of CLC, demographic information and results of immunohistochemistry were statistically analyzed to validate the correlation. Results Besides the pattern of frog spawn-like blisters, lymphangioma also presented as either transparent or pigmented with dark-red to whitish/yellowish shades. Moreover, lymphangioma manifested as a pattern of dermatofibroma. Furthermore, CD31 was detected in the flattened endothelium and only present in dilated spaces containing enough blood or lymph components. Limitations：This study is limited by its retrospective nature and statistical power. Conclusion Dermoscopy is useful in the diagnosis of CLC. CD31 positive staining and cystic-dilated spaces showed flattened inner and outer endothelia with a hypopyon-like shape and blisters resembling frog spawn patterns are the two diagnostic features of CLC. These features can assist in the diagnosis of CLC.